جوانب حضارية للجزائر العثمانية خلال القرن 16 من خلال كتابي تاريخ ملوك الجزائر وطبوغرافيا الجزائر لديغو هايدو - عطية ملاك (My University, 2025)
Abstract : This study presented an exposition of the civilization alfacets of Ottoman Algeria, based on the works of the historian Diego Haedo: "History of the Kings of Algiers" and "Topography and General History of Algeria." The study commenced with an introductory chapter that aimed to introduce the author Haedo and elucidate his aforementioned works, as well as provide a general overview of the prevailing conditions in Algeria during the Ottoman era. The main body of the study comprised two chapters. The first, entitled "Political and Military Life," addressed the political dimension in terms of the governmental structure and Algeria's internal and external relations. The military aspect, conversely, examined the Algerian navy and the details of Charles V's expedition against Algeria sand the Battle of Mazagran. The second chapter, titled "Social and Cultural Life,"encompassed two sub-sections. The first addressed the social aspect, incorporating the demographic composition of Algerian society, the Algerian woman, and the attire of Algerians. The second sub-section explored the cultural aspect, detailing the customs and traditions observed in marriage, child-rearing, and circumcision ceremonies, in addition to the celebrations of religious occasions such as the month of Ramadan and the Eid al-Fitr and Eid al-Adha festivals. Furthermore, It touched upon the languages spoken in Ottoman Algeria and the types of currencies utilized at that time. ------------------------ الملخص: تناولت هذه الدراسة عرضا لموضوع جوانب حضارية للجزائر العثمانية اعتماداً على كتابي "تاريخ ملوك الجزائر" و"الطبوغرافيا وتاريخ الجزائر العام"للمؤرخ دييغو هايدو، وقد استهلت الدراسة بفصل تمهيدي هدف إلى التعريف بالمؤلف هايدو و شرح مؤلّفيه، و تقديم لمحة عامة حول الأوضاع السائدة في الجزائر إبان الحكم العثماني. وتضمن متن الدراسة فصلين اثنين: الأول، تحت عنوان "الحياة السياسية والعسكرية"، تناول الشق السياسي من حيث هيكل الحكم وعلاقات الجزائر الداخلية والخارجية. أما الجانب العسكري، فقد استعرض البحرية الجزائرية وتفاصيل حملة شارلكان على الجزائر ومعركة مزغران. أما الفصل الثاني، والمعنون بـ "الحياة الاجتماعية والثقافية"، فقد اشتمل على مبحثين فرعيين: الأول تناول الجانب الاجتماعي، ضمّ التركيبة السكانية للمجتمع الجزائري، و المرأة الجزائرية ، ولباس الجزائريين. في حين استعرض المبحث الثاني الجانب الثقافي، متناولا العادات والتقاليد المتبعة في الزواج وتربية الأطفال ومراسم الختان، بالإضافة إلى الاحتفالات بالمناسبات الدينية كشهر رمضان وعيدي الفطر والأضحى. كما تطرق إلى اللغات المتداولة في الجزائر العثمانية وأنواع العملات المستخدمة آنذاك. ---------------------------- Résumé : Cette étude examine les aspects culturels de l’Algérie ottomane, en s’appuyant sur les ouvrages « Histoire des rois d’Algérie » et « Topographie et histoire générale de l’Algérie » de l’historien Diego Haedo. Elle débute par un chapitre introductif présentant Haedo et ses auteurs, et offrant un aperçu des conditions prévalant en Algérie sous la domination ottomane. L’étude comprend deux chapitres : le premier, intitulé « Vie politique et militaire », aborde l’aspect politique, notamment la structure du gouvernement et les relations internes et externes de l’Algérie. Le volet militaire examine la marine algérienne et les détails de la campagne de Charles Quint contre l’Algérie et de la bataille de Mazagran. Le deuxième chapitre, intitulé « Vie sociale et culturelle », comprend deux sous-thèmes : le premier aborde l’aspect social, englobant la composition démographique de la société algérienne, les femmes algériennes et le costume algérien. La deuxième section explore l'aspect culturel, couvrant les coutumes et traditions liées au mariage, à l'éducation des enfants et aux cérémonies de circoncision, ainsi que les célébrations religieuses telles que le Ramadan, l'Aïd el-Fitr et l'Aïd el-Adha. Elle aborde également les langues parlées en Algérie ottomane et les types de monnaie utilisés à l'époque.
Keywords: جوانب حضارية، الجزائر العثمانية، القرن 16، كتابي تاريخ ملوك الجزائر وطبوغرافيا الجزائر لديغو هايدو